2016
DOI: 10.1186/s12977-016-0253-1
|View full text |Cite
|
Sign up to set email alerts
|

The interferon-induced antiviral protein PML (TRIM19) promotes the restriction and transcriptional silencing of lentiviruses in a context-specific, isoform-specific fashion

Abstract: BackgroundThe promyelocytic leukemia (PML) protein, a type I interferon (IFN-I)-induced gene product and a member of the tripartite motif (TRIM) family, modulates the transcriptional activity of viruses belonging to various families. Whether PML has an impact on the replication of HIV-1 has not been fully addressed, but recent studies point to its possible involvement in the restriction of HIV-1 in human cells and in the maintenance of transcriptional latency in human cell lines in which HIV-1 is constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 71 publications
0
55
0
Order By: Relevance
“…Interestingly, TRIM22 was found to interact with HDAC, a repressor of HIV-1 viral transcription, and this interaction was necessary for continual proviral suppression [144]. Both human and murine TRIM19 are capable of preventing HIV-1 replication by downregulating expression of the viral LTR [145,146]. This effect holds true for several isoforms of TRIM19, including I, II, IV and VI, which can be enhanced further by IFN-I stimulation [145].…”
Section: Cooperative Antiviral Mechanisms Of Trim22 and Trim19mentioning
confidence: 99%
“…Interestingly, TRIM22 was found to interact with HDAC, a repressor of HIV-1 viral transcription, and this interaction was necessary for continual proviral suppression [144]. Both human and murine TRIM19 are capable of preventing HIV-1 replication by downregulating expression of the viral LTR [145,146]. This effect holds true for several isoforms of TRIM19, including I, II, IV and VI, which can be enhanced further by IFN-I stimulation [145].…”
Section: Cooperative Antiviral Mechanisms Of Trim22 and Trim19mentioning
confidence: 99%
“…In addition, PML inhibits HIV-1 transcription in MEFs, an effect that we did not observe in human cells (32). Thus, it is conceivable for PML to have an impact on TRIM5α-mediated restriction of HIV-1 in this specific cellular environment.…”
Section: Resultsmentioning
confidence: 55%
“…Accordingly, we previously showed that PML was important for the efficient inhibition of HIV-1 by IFN-I in MEFs (32). Although HIV-1 is also readily inhibited by IFN-I in a variety of human cell types, as illustrated in our study, we find that this effect is not affected by knocking out PML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that after herpes simplex virus (HSV) infection, the viral genomes rapidly become associated with PML‐BNs . There is another study indicated that PML downregulates the expression of the HIV‐1 LTR‐driven GFP and confers on the MEFs a restriction to HIV‐1 by affecting the reverse transcription and interfering with HIV‐1 transcription, whereas PML depletion renders human T cells susceptible to HIV‐1 and SIV . Daxx could interfere with reverse transcription and inhibit retroviral infection.…”
Section: Trims Primarily Function As E3‐ligases To Protect the Host Fmentioning
confidence: 99%